Survey and Documentation of Some Traditionally used Medicinal Herbs found in Manipur - Khan, M. R.; Sharma, L. D. (Indian Forester, 2024)
Plants are exceptional origin of medicines, spices and aromatics; moreover have multiple household and ritual uses. The remote villages of valley people practices folk medicines to take care of their health and related problems primarily from the plant sources. So, there is necessary to set up the scientific basis for their therapeutic actions, which may bring to visibility picture on effective drugs. Keeping this in view efforts are underway to search for better intellect of qualitative, quantitative chemical composition and to explore the antimicrobial activity as well as any other health diseases. A survey has been conducted and collected information through interview and discussion among the knowledgeable persons of the study sites, on the valuable plants used by the people of valley districts. During the investigation it has been recorded 150 species belonging to 50 genera and 30 families which are widely used as value-added products. This investigation showed that for proper documentation and traditional knowledge of practicing the medicinal plant for development of value-added products such as spices, medicines and aromatics.